Adaptive speech enhancement with varying noise backgrounds - Kϋhnapfel, Thorsten; Tan, Tele; Venkatesh, Svetha; Igel, B.; Nordholm, Sven (IEEE, 2008)
We present a new approach for speech enhancement in the presence of non-stationary and rapidly changing background noise. A distributed microphone system is used to capture the acoustic characteristics of the environment. The input of each microphone is then classified either as speech or one of the predetermined noise types. Further enhancement of speech in respective microphones is carried out using a modified spectral subtraction algorithm that incorporates multiple noise models to quickly adapt to rapid background noise changes. Tests on real world speech captured under diverse conditions demonstrate the effectiveness of this method.